Explaining the negative effects of workplace incivility on family lives: a moderated mediation model of surface acting and resource-providing variables - Gu, Yuanbo; Wang, Cuiping; Ma, Jinhua (Frontiers in Psychology, 2024)
The effects of workplace incivility have been understudied in educational settings.To expand incivility research to educational professions, the present research investigates whether, how, and when workplace incivility deriving from different sources (coworkers, supervisors, and outsiders) is related to work-to-family interference (WFI) of preschool teachers. Drawing on the conservation of resources theory, the present study proposes that workplace incivility and subsequent maladaptive emotion labor strategies (i.e., surface acting) jointly create a resource-depletion mechanism contributing to elevated WFI and two resource-providing variables (supervisor work-family support and psychological detachment after hours) function as potential mitigating factors to break the resource-depletion mechanism. This study used a female-dominated sample (i.e., preschool teachers) found that workplace incivility from insiders (supervisors and coworkers respectively) and external stakeholders (child's family members) all positively linked to WFI, and surface acting mediated these relationships. Moreover, moderated mediation analyses indicated that psychological detachment buffered the mediated effect of surface acting on WFI, whereas supervisor work-family support did not. Findings deepen the understanding of why and when workplace incivility influences employees' family lives, as well as point to future intervention strategies.